2011
DOI: 10.1111/j.1834-7819.2011.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe adverse reactions to dental local anaesthetics: prolonged mandibular and lingual nerve anaesthesia

Abstract: Background: Prolonged anaesthesia may occur following dental local anaesthetic blocks. This paper reviews the possible mechanisms of injury. Direct injury to the nerve by the needle, although commonly thought to be the mechanism, is unlikely. It is much more likely that the injury is from neurotoxicity and ⁄ or interference with the vascularization of the nerve. Methods: Estimation of the frequency of injury was complicated by the fact that although local anaesthetics are prescription-only (S4) drugs, they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 19 publications
1
50
0
5
Order By: Relevance
“…The recent Australian study found an incidence of 1 in 27 415 although this figure has wide confidence limits. 2 Prolonged anaesthesia may also occur when lower 2% local anaesthetic agents are used. 2 The key issue is that the evidence indicates that there is a greater risk with a higher concentration of local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent Australian study found an incidence of 1 in 27 415 although this figure has wide confidence limits. 2 Prolonged anaesthesia may also occur when lower 2% local anaesthetic agents are used. 2 The key issue is that the evidence indicates that there is a greater risk with a higher concentration of local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prolonged anaesthesia may also occur when lower 2% local anaesthetic agents are used. 2 The key issue is that the evidence indicates that there is a greater risk with a higher concentration of local anaesthetics. The increased risk is conservatively estimated at 5-to 7-fold.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations